Environmental effectiveness of GAEC cross-compliance Standard 2.1 ‘Maintaining the level of soil organic matter through management of stubble and crop residues’ and economic evaluation of the competitiveness gap for farmers - Domenico Ventrella; Nino Virzì; Francesco Intrigliolo; Massimo Palumbo; Michele Cambrea; Alfio Platania; Fabiola Sciacca; Stefania Licciardello; Antonio Troccoli; Mario Russo; Rosa Francaviglia; Ulderico Neri; et al. (Italian Journal of Agronomy)
Within the Project MO.NA.CO. the Environmental effectiveness of GAEC cross-compliance Standard 2.2 ‘Maintaining the level of soil organic matter through management of stubble and crop residues’ and economic evaluation of the competitiveness gap for farmers were evaluated. The monitoring was performed in eight experimental farms of the Council for agricultural research and economics (CREA), distributed throughout Italy and with different soil and climatic conditions. Yield parameters and several components of soil organic matter were evaluated in two contrasting treatments applied to one-year rotation of winter durum wheat and maize: i) incorporation into the soil of crop residues (Factual treatment) and ii) burning or removal of crop residues (Counterfactual treatment). The application of the standard ‘crop residue management’ has showed contrasting results with differences (for yield and soil) between the two treatments resulted almost always non significant. The analysis of economic competitiveness gap showed that the CR incorporation is more expensive than CR burning or removal, but the economic disadvantage can be considered rather small and thus easily compensated by Community aids. Therefore, the soil incorporation of crop residues can be considered a ‘good agricultural practice’ that does not penalize farmers in terms of production and cost and at the same time contributes to the maintenance of fertility and soil biodiversity. On the contrary, the removal and burning of residues result in a low or no-addition of organic matter into the soil. Moreover, burning can contribute to decrease the biodiversity and to increase the risk of air pollution, fires and road accidents.